2017
DOI: 10.1021/acs.est.7b02985
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Cyanobacterial Blooms Using Nanosilica: A Biomineralization-Inspired Strategy

Abstract: Cyanobacterial blooms represent a significant threat to global water resources because blooming cyanobacteria deplete oxygen and release cyanotoxins, which cause the mass death of aquatic organisms. In nature, a large biomass volume of cyanobacteria is a precondition for a bloom, and the cyanobacteria buoyancy is a key parameter for inducing the dense accumulation of cells on the water surface. Therefore, blooms will likely be curtailed if buoyancy is inhibited. Inspired by diatoms with naturally generated sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Some "abnormal" crystallization behavior in biomineralization-such as abnormally high Mg content in minerals, abnormal stability of precursor phases, abnormally precise control of crystal phases and orientations, abnormal reproducibility, abnormally uniform size and spatial distributions of minerals, and the vital effects [39,191]-would benefit from these theoretical advances. The fundamental and quantitative investigation of a small well-defined system would have a large impact on the understanding of biomineralization mechanisms, which would inspire the development of many functional materials with unlimited patterns and morphologies to solve global problems regarding the environment [192][193][194], energy [195][196][197][198], and healthcare [199][200][201][202].…”
Section: Discussionmentioning
confidence: 99%
“…Some "abnormal" crystallization behavior in biomineralization-such as abnormally high Mg content in minerals, abnormal stability of precursor phases, abnormally precise control of crystal phases and orientations, abnormal reproducibility, abnormally uniform size and spatial distributions of minerals, and the vital effects [39,191]-would benefit from these theoretical advances. The fundamental and quantitative investigation of a small well-defined system would have a large impact on the understanding of biomineralization mechanisms, which would inspire the development of many functional materials with unlimited patterns and morphologies to solve global problems regarding the environment [192][193][194], energy [195][196][197][198], and healthcare [199][200][201][202].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to better obtain the control effects of protozoa in controlling harmful cyanobacteria, it is necessary to consider not only choosing an appropriate time and combining physical methods for disaggregating colonial cyanobacteria , but also determining a rapid cultivation method for these protozoa, as the abundance of protozoa in the field is far from that which can effectively control harmful algae. In addition, we also should generally consider the roles of other aquatic organisms during different periods of cyanobacterial blooms ,, and other methods including chemical and material addition, nutrient control and engineering techniques. , From the perspective of lake management, we first need to comprehensively consider the methods of controlling cyanobacterial blooms on the basis of various environmental factors, complex food webs, and cyanobacterial bloom-forming processes. In addition, we also should focus on the potential impacts of these control methods on an aquatic ecosystem to avoid additional negative influences on interrupting ecological balance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study demonstrated that the EDTA can also donate the electron to efficiently reduce the NADP to NADPH in the presence of metal oxides. Furthermore, those metal oxides reported for cofactor regeneration may also inhibit the growth of cyanobacteria (Comotto et al, 2014; Xiong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%